Inovasi pada Organisasi Pemerintah: Tahapan dan Dinamika - Ridlowi Ridlowi; Fathul Himam (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
Innovation has been identical with the use of new ways to gain the effectiveness and efficiency of a product, service, or methodology by a profit organization in order to face the business competition. The aim of this research is to see the dynamics that happen on innovation process run by government organization by taking case study on Computer Assisted Test (CAT) based employee selection system in National Civil Service Agency. The data are gathered through deep-interview to five research respondents by using qualitative approach. The results show that there are three main dimensions in the development proses of CAT system innovation: building the base of organization knowledge, designing innovation system, and developing system of continuity. The dimension of developing continuity system has become the unique characteristic in this study in comparison with the other results in regard to the process and innovation steps. Innovation in CAT system is a self-actualization of government organization to acquire and maintain its programs and authorities.